The Ceremonial Tradition of Tabut According to the Perspective of Nahdlatul Ulama (NU) and Muhammadiyah Leaders In Bengkulu City - Anisah Albayani; Bitoh Purnomo (CV. Doki Course and Training, 2023)
In the perspective of Islamic law tradition is a custom ('urf) which is one that is accepted by common sense. The Ark in the city of Bengkulu is a multi-storey building decorated with colors and is 10 meters high. The subject of study in this research is how the perspective of Nahdlatul Ulama and Muhammadiyah figures regarding the tradition of the ark ceremony in the city of Bengkulu. The aim of this study is to examine the perspectives of Nahdlatul Ulama figures and Muhammadiyah figures regarding the tradition of the ark ceremony in the city of Bengkulu and find out the similarities and differences in the opinions of the two figures. This research is a qualitative research with the type of field (Field Research). The approach method used is the comparative approach. According to Nahdlatul Ulama figures, the ark ceremony tradition is well preserved because according to him there is no element of polytheism, while according to Muhammadiyah figures, the ark ceremony tradition is not well preserved because the ritual contains many polytheistic matters. The conclusion of this research is that there are three points of difference of opinion between Nahdlatul Ulama figures and Muhammadiyah figures regarding the tabut ceremony tradition, namely the meaning of the implementation of the tabut ceremony tradition, the shirk element of the tabut ceremony tradition, and the ritual activities of the tabut ceremony tradition. It is hoped that this research can provide students and the public with an understanding of how the perspectives of Nahdlatul Ulama and Muhammadiyah figures in the city of Bengkulu.